Future Modulation of Gut Microbiota: From Eubiotics to FMT, Engineered Bacteria, and Phage Therapy - Carlo Airola; Andrea Severino; Serena Porcari; William Fusco; Benjamin H. Mullish; Antonio Gasbarrini; Giovanni Cammarota; Francesca Romana Ponziani; Gianluca Ianiro (MDPI AG, 2023)
The human gut is inhabited by a multitude of bacteria, yeasts, and viruses. A dynamic balance among these microorganisms is associated with the well-being of the human being, and a large body of evidence supports a role of dysbiosis in the pathogenesis of several diseases. Given the importance of the gut microbiota in the preservation of human health, probiotics, prebiotics, synbiotics, and postbiotics have been classically used as strategies to modulate the gut microbiota and achieve beneficial effects for the host. Nonetheless, several molecules not typically included in these categories have demonstrated a role in restoring the equilibrium among the components of the gut microbiota. Among these, rifaximin, as well as other antimicrobial drugs, such as triclosan, or natural compounds (including evodiamine and polyphenols) have common pleiotropic characteristics. On one hand, they suppress the growth of dangerous bacteria while promoting beneficial bacteria in the gut microbiota. On the other hand, they contribute to the regulation of the immune response in the case of dysbiosis by directly influencing the immune system and epithelial cells or by inducing the gut bacteria to produce immune-modulatory compounds, such as short-chain fatty acids. Fecal microbiota transplantation (FMT) has also been investigated as a procedure to restore the equilibrium of the gut microbiota and has shown benefits in many diseases, including inflammatory bowel disease, chronic liver disorders, and extraintestinal autoimmune conditions. One of the most significant limits of the current techniques used to modulate the gut microbiota is the lack of tools that can precisely modulate specific members of complex microbial communities. Novel approaches, including the use of engineered probiotic bacteria or bacteriophage-based therapy, have recently appeared as promising strategies to provide targeted and tailored therapeutic modulation of the gut microbiota, but their role in clinical practice has yet to be clarified. The aim of this review is to discuss the most recently introduced innovations in the field of therapeutic microbiome modulation.